Pribumi Digital Moderat: Profil Kecakapan Komunikasi Digital Generasi Z - Muhammad Badri (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2022)
The development of digital media encourages the growth of creativity as well as raises various ethical issues. To encourage a positive impact, users must have digital communication skills. This study aims to determine the digital communication skills of Generation Z, and the study was conducted in Riau Province. This study uses a quantitative approach with a survey method on 150 generation Z representing urban and rural areas. The research instrument uses four dimensions of digital skills: information, communication, problem-solving, and content development. This study found that a high percentage of all information skills indicators showed that Generation Z's digital literacy was relatively good because they could choose credible websites and social media. Communication skills show a high percentage on all indicators, even very high indicators of the ability to communicate in a digital environment and respect differences, such as religion, culture, gender, and social status. Digital problem-solving skills show a high percentage on all indicators, especially the ability to decide on the use of digital platforms according to their goals and needs. Meanwhile, content development skills tend to be low in producing creative content and managing rights and licenses. This finding concludes that Generation Z is a digital native who is moderate to digital cultural differences and responsive to the development of digital media. This study recommends strengthening digital literacy, especially the development of creative content and intellectual property.